If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3g + 2(-6 + 3g) = 1 + -1g 3g + (-6 * 2 + 3g * 2) = 1 + -1g 3g + (-12 + 6g) = 1 + -1g Reorder the terms: -12 + 3g + 6g = 1 + -1g Combine like terms: 3g + 6g = 9g -12 + 9g = 1 + -1g Solving -12 + 9g = 1 + -1g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add 'g' to each side of the equation. -12 + 9g + g = 1 + -1g + g Combine like terms: 9g + g = 10g -12 + 10g = 1 + -1g + g Combine like terms: -1g + g = 0 -12 + 10g = 1 + 0 -12 + 10g = 1 Add '12' to each side of the equation. -12 + 12 + 10g = 1 + 12 Combine like terms: -12 + 12 = 0 0 + 10g = 1 + 12 10g = 1 + 12 Combine like terms: 1 + 12 = 13 10g = 13 Divide each side by '10'. g = 1.3 Simplifying g = 1.3
| 4x+15=-5 | | x-2/8-4x | | F=1.8*91+32 | | 82/3=2v-91/2 | | -5x-4y=-36 | | 43=-5b+2(2b+18) | | 5x+y=-41 | | (4a+2b)(a-b)= | | 114-2x=25+24 | | a/4+10=22 | | 3x^3+6x^2-57x-60= | | 2x+4y=34 | | 8x+4(3x/5)=3048 | | 3(2x-1)=5x+4 | | 2x+4y=-7 | | 8(w+3)=4w-4 | | 3x/2+5=3x-1 | | R=-20+6+500 | | 92=4v | | log(8)32.768=x | | 3(2x+7)=11x+1 | | (5p+2)(p+4)=1 | | 0.1x+14.2=x-2.54 | | y/2=52 | | -5x+y=-63 | | 2x-54=-22 | | -11-3x=7-7x | | n+2=3n^2 | | -0.9x+4.81=-0.7x+8.41 | | f(x)=X^3+4x^2-9x-36 | | 8(381+-0.5y)+4y=3048 | | (a-4)(a+10)=-17 |